Wear-resistant unglazed polished porcelain tile and preparation method thereof

By coating the enhanced wear-resistant composite materials with modified shellac resin and other materials on the brick layer of the ceramic polished tiles, the problem of anti-fouling liquid of existing ceramic polished tiles is solved, and higher wear resistance and pollution resistance are achieved and thermal shock resistance.

CN119430857AActive Publication Date: 2025-02-14GUANGDONG TIANBI CERAMICS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411592578.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The anti-fouling liquid of existing ceramic polished tiles is prone to fall off after wear and loses its protective effect.

Method used

The brick layer is prepared using composite materials including recycling ceramic powder, sintered fly ash, nano Lu2O3, hydroxyapatite and calcium-magnesium silicon, and the surface of the brick layer is coated with modified shellac resin, hollow glass microspheres, and 2-acrylamide. Reinforced wear-resistant composite materials for materials such as base-2-methylpropanesulfonic acid and carboxymethylcellulose.

Benefits of technology

It improves the wear resistance and stain resistance of the brick layer, enhances the thermal shock resistance and strength of the brick, and prevents the coating from falling off.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a wear-resistant unglazed polished porcelain tile and a preparation method thereof, and belongs to the technical field of unglazed polished porcelain tiles, the wear-resistant unglazed polished porcelain tile comprises a tile layer and a reinforced wear-resistant layer coated on the surface of the tile layer, a bottom blank is prepared by recycling ceramic micro powder, sintered fly ash, nano Lu2O3, hydroxyapatite and a calcium-magnesium-silicon composite material, and the bottom blank is prepared into a finished product. The preparation method comprises the following steps: modifying shellac resin by using hollow glass microspheres of 100-200 [mu] m and polyphosphoric acid, then preparing a reinforced wear-resistant composite material by using the modified shellac resin, hollow glass microspheres of 400-500 [mu] m, 2-acrylamido-2-methylpropanesulfonic acid, carboxymethyl cellulose and 120 parts of a solvent, sintering and cooling a bottom blank, and coating the surface of the bottom blank with the reinforced wear-resistant composite material, the unglazed polished porcelain tile with the polished surface layer is obtained. The prepared unglazed polished porcelain tile is high in surface hardness, good in wear resistance, not prone to falling off, good in antifouling property, high in thermal shock resistance and high in tile strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of unglazed polished porcelain tiles, and in particular to a wear-resistant unglazed polished porcelain tile and a preparation method thereof. Background Art

[0002] Polished porcelain tiles are a type of bright tile made by polishing the surface of the whole tile body. It has the advantages of smooth surface, stain resistance, and good visual effect.

[0003] CN118373694A discloses a production method of ceramic polished tiles and the ceramic polished tiles produced therefrom, comprising the following steps: adding a foaming agent, a water reducing agent and a body reinforcing agent during wet grinding to obtain body slurry; sieving the slurry obtained by wet grinding, spray drying the sifted slurry to obtain powder, and storing the powder in a warehouse for aging; placing the aged powder in a mold and pressing it into a body, and then drying the body in a drying oven; sending the dried body into a kiln for firing and shaping to obtain a semi-finished product; taking out the fired semi-finished product, polishing and grinding the semi-finished product after cooling to make the surface of the semi-finished product smooth, then spraying an antifouling liquid on the surface of the semi-finished product, and repeatedly grinding at least twice, and then heat treating to obtain a finished ceramic polished tile.

[0004] However, there are the following problems: the antifouling liquid only has an antifouling effect, and after a period of wear, it is easy to fall off from the surface, resulting in a loss of protective effect on the bricks.

[0005] Based on this, the present invention designs a wear-resistant unglazed polished porcelain tile and a preparation method thereof to solve the above problems. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a wear-resistant unglazed polished porcelain tile and a preparation method thereof.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A wear-resistant unglazed polished porcelain tile comprises a brick layer and a reinforced wear-resistant layer coated on the surface of the brick layer, wherein the brick layer comprises the following raw materials in parts by weight: 75-105 parts of recycled ceramic micropowder, 14-18 parts of sintered fly ash, 1.6-4.0 parts of nano Lu2O3, 5-11 parts of hydroxyapatite, and 12-27 parts of calcium-magnesium-silicon composite material;

[0009] The enhanced wear-resistant layer comprises the following raw materials in parts by weight: 14-21 parts of shellac resin, 4-7 parts of hollow glass microspheres, 18-25 parts of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), 4-10 parts of carboxymethyl cellulose, and 14-21 parts of polyphosphoric acid (PPA).

[0010] Furthermore, the calcium-magnesium-silicon composite material is prepared by high-temperature melting and spinning of calcium stone powder, silica stone powder and magnesia, and has the following components: 15-18% CaO, 15-20% MgO, and the remainder SiO2.

[0011] Furthermore, the sintered fly ash is obtained by calcining fly ash at 330-400° C. and then grinding it.

[0012] Furthermore, the particle size of the hollow glass microspheres is 100-500 μm, and the ball breakage rate is less than 10%.

[0013] Furthermore, the hollow glass microspheres include the following two particle sizes: 100-200 μm 32-48%; 400-500 μm remainder.

[0014] Furthermore, the weight ratio of the shellac resin to polyphosphoric acid (PPA) is controlled at 1:1.

[0015] A method for preparing the wear-resistant unglazed polished porcelain tile comprises the following steps:

[0016] 1. Preparation of Brick Layer

[0017] Mix 75-105 parts of recycled ceramic micropowder, 14-18 parts of sintered fly ash, 1.6-4.0 parts of nano-Lu2O3, 5-11 parts of hydroxyapatite, and 12-27 parts of calcium-magnesium-silicon composite material, press to obtain a base blank, and cool after sintering;

[0018] 2. Preparation of reinforced wear-resistant composite materials

[0019] Adding hollow glass microspheres of 100 to 200 μm and shellac resin to polyphosphoric acid (PPA), and subjecting the mixture to a modification reaction at 75 to 81° C. for 1 to 3 hours to obtain a modified shellac resin; then mixing the modified shellac resin, hollow glass microspheres of 400 to 500 μm, 18 to 25 parts of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 4 to 10 parts of carboxymethyl cellulose and 90 to 130 parts of a solvent, subjecting the mixture to a stirring reaction at 105 to 110° C. for 1.3 to 2 hours to obtain a reinforced wear-resistant composite material;

[0020] 3. Coating the reinforced wear-resistant composite material on the surface of the brick layer and drying it to obtain an unglazed polished porcelain tile with a polished surface layer.

[0021] Furthermore, the drying temperature is 60-75°C.

[0022] Furthermore, the sintering includes the following steps: sintering at 500-600°C for 10-25 min, then sintering at 900-1000°C for 30-50 min, and finally sintering at 1300-1400°C for 1.5-2.5 h.

[0023] Furthermore, after sintering, cooling and polishing, the reinforced wear-resistant composite material is coated on the surface of the brick layer.

[0024] In order to better achieve the purpose of the present invention, the present invention also provides a wear-resistant unglazed polished porcelain tile and a preparation method thereof.

[0025] Compared with the prior art, the present invention has the following beneficial effects: the present invention prepares a base blank by recycling ceramic micropowder, sintered fly ash, nano Lu2O3, hydroxyapatite, and calcium magnesium silicon composite material, and uses 100-200 μm hollow glass microspheres and polyphosphoric acid (PPA) to modify shellac resin, and then uses modified shellac resin, 400-500 μm hollow glass microspheres, 2-acrylamide-2-methylpropanesulfonic acid (AMPS), carboxymethyl cellulose and 120 parts of solvent (water) to prepare an enhanced wear-resistant composite material, and the base blank is sintered and cooled and then polished, and then the surface is coated with the enhanced wear-resistant composite material to obtain an unglazed polished porcelain tile with a polished surface layer. The prepared unglazed polished porcelain tile has high surface hardness, good wear resistance, is not easy to fall off, has good anti-fouling performance, high thermal shock resistance, and high tile strength. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1: In some embodiments, a wear-resistant unglazed polished porcelain tile comprises a brick layer and a reinforced wear-resistant layer coated on the surface of the brick layer, wherein the brick layer comprises the following raw materials in parts by weight: 75 parts of recycled ceramic micropowder, 14 parts of sintered fly ash, 1.6 parts of nano Lu2O3, 5 parts of hydroxyapatite, and 12 parts of calcium-magnesium-silicon composite material; the calcium-magnesium-silicon composite material is prepared by high-temperature melting and spinning of calcium stone powder, silica powder, and magnesia, and the composition is: 15% CaO, 15% MgO, and the balance SiO2; the sintered fly ash is obtained by calcining fly ash at 330°C and then grinding; the reinforced wear-resistant layer comprises the following raw materials in parts by weight: 14 parts of shellac resin, 4 parts of hollow glass microspheres, 18 parts of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 4 parts of carboxymethyl cellulose, and 14 parts of polyphosphoric acid (PPA); the hollow glass microsphere breakage rate is less than 10%. The hollow glass microspheres include the following two particle sizes: 100-200 μm 32%; 400-500 μm remainder.

[0028] The method for preparing the wear-resistant unglazed polished porcelain tile comprises the following steps:

[0029] 1. Preparation of brick layer: Mix the recycled ceramic powder, sintered fly ash, nano Lu2O3, hydroxyapatite and calcium magnesium silicon composite material, press to obtain the base blank, then sinter at 500℃ for 10min, then sinter at 900℃ for 30min, and finally sinter at 1300℃ for 1.5h; polish after cooling;

[0030] 2. Preparation of enhanced wear-resistant composite materials: adding 100-200 μm hollow glass microspheres and shellac resin to polyphosphoric acid (PPA), placing at 75°C for modification reaction for 1 hour to obtain modified shellac resin; then mixing the modified shellac resin, 400-500 μm hollow glass microspheres, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), carboxymethyl cellulose and 90 parts of solvent (water), placing at 105°C for stirring reaction for 1.3 hours to obtain an enhanced wear-resistant composite material;

[0031] 3. Coat the surface of the brick layer with the enhanced wear-resistant composite material and dry it at 60°C to obtain an unglazed polished porcelain tile with a polished surface layer. The thickness of the enhanced wear-resistant layer can be about 0.5 mm.

[0032] Embodiment 2: In some embodiments, a wear-resistant unglazed polished porcelain tile comprises a brick layer and a reinforced wear-resistant layer coated on the surface of the brick layer, wherein the brick layer comprises the following raw materials in parts by weight: 105 parts of recycled ceramic micropowder, 18 parts of sintered fly ash, 4.0 parts of nano Lu2O3, 11 parts of hydroxyapatite, and 27 parts of calcium-magnesium-silicon composite material; the calcium-magnesium-silicon composite material is prepared by high-temperature melting and spinning of calcium stone powder, silica powder, and magnesia, and the composition is: 18% CaO, 20% MgO, and the balance SiO2; the sintered fly ash is obtained by calcining fly ash at 400°C and then grinding; the reinforced wear-resistant layer comprises the following raw materials in parts by weight: 21 parts of shellac resin, 7 parts of hollow glass microspheres, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) 25 parts, 10 parts of carboxymethyl cellulose, and 21 parts of polyphosphoric acid (PPA); the ball breakage rate of the hollow glass microspheres is less than 10%. The hollow glass microspheres include the following two particle sizes: 100-200 μm 48%; 400-500 μm remainder.

[0033] The method for preparing the wear-resistant unglazed polished porcelain tile comprises the following steps:

[0034] 1. Preparation of brick layer: Mix the recycled ceramic powder, sintered fly ash, nano Lu2O3, hydroxyapatite, and calcium magnesium silicon composite material, press to obtain the base blank, then sinter at 600℃ for 25min, then sinter at 1000℃ for 50min, and finally sinter at 1400℃ for 2.5h; polish after cooling;

[0035] 2. Preparation of enhanced wear-resistant composite materials: adding hollow glass microspheres of 100 to 200 μm and shellac resin to polyphosphoric acid (PPA), placing at 81°C for modification reaction for 3 hours to obtain modified shellac resin; then mixing the modified shellac resin, hollow glass microspheres of 400 to 500 μm, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), carboxymethyl cellulose and 130 parts of solvent (water), placing at 110°C for stirring reaction for 2 hours to obtain an enhanced wear-resistant composite material;

[0036] 3. Coat the surface of the brick layer with the enhanced wear-resistant composite material and dry it at 75°C to obtain an unglazed polished porcelain tile with a polished surface layer. The thickness of the enhanced wear-resistant layer can be about 0.5 mm.

[0037] Embodiment 3: In some embodiments, a wear-resistant unglazed polished porcelain tile comprises a brick layer and a reinforced wear-resistant layer coated on the surface of the brick layer, wherein the brick layer comprises the following raw materials in parts by weight: 85 parts of recycled ceramic micropowder, 15 parts of sintered fly ash, 2 parts of nano Lu2O3, 7 parts of hydroxyapatite, and 15 parts of calcium-magnesium-silicon composite material; the calcium-magnesium-silicon composite material is prepared by high-temperature melting and spinning of calcium stone powder, silica powder, and magnesia, and the composition is: 16% CaO, 17% MgO, and the balance SiO2; the sintered fly ash is obtained by calcining fly ash at 350°C and then grinding; the reinforced wear-resistant layer comprises the following raw materials in parts by weight: 15 parts of shellac resin, 5 parts of hollow glass microspheres, 20 parts of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 5 parts of carboxymethyl cellulose, and 18 parts of polyphosphoric acid (PPA); the ball breakage rate of the hollow glass microspheres is less than 10%. The hollow glass microspheres include the following two particle sizes: 100-200 μm 38%; 400-500 μm remainder.

[0038] The method for preparing the wear-resistant unglazed polished porcelain tile comprises the following steps:

[0039] 1. Preparation of brick layer: Mix the recycled ceramic powder, sintered fly ash, nano Lu2O3, hydroxyapatite and calcium magnesium silicon composite material, press to obtain the base blank, then sinter at 530℃ for 15min, then sinter at 960℃ for 35min, and finally sinter at 1350℃ for 2h; polish after cooling;

[0040] 2. Preparation of enhanced wear-resistant composite materials: adding hollow glass microspheres of 100 to 200 μm and shellac resin to polyphosphoric acid (PPA), placing at 79° C. for modification reaction for 2 hours to obtain modified shellac resin; then mixing the modified shellac resin, hollow glass microspheres of 400 to 500 μm, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), carboxymethyl cellulose and 100 parts of solvent (water), placing at 108° C. for stirring reaction for 1.6 hours to obtain an enhanced wear-resistant composite material;

[0041] 3. Coat the surface of the brick layer with the enhanced wear-resistant composite material and dry it at 65°C to obtain an unglazed polished porcelain tile with a polished surface layer. The thickness of the enhanced wear-resistant layer can be about 0.5 mm.

[0042] Embodiment 4: In some embodiments, a wear-resistant unglazed polished porcelain tile comprises a brick layer and a reinforced wear-resistant layer coated on the surface of the brick layer, wherein the brick layer comprises the following raw materials in parts by weight: 90 parts of recycled ceramic micropowder, 16 parts of sintered fly ash, 3 parts of nano Lu2O3, 10 parts of hydroxyapatite, and 18 parts of calcium magnesium silicon composite material; the calcium magnesium silicon composite material is prepared by high-temperature melting and spinning of calcium stone powder, silica powder, and magnesia, and the composition is: 17% CaO, 19% MgO, and the balance SiO2; the sintered fly ash is obtained by calcining fly ash at 380°C and then grinding; the reinforced wear-resistant layer comprises the following raw materials in parts by weight: 20 parts of shellac resin, 6 parts of hollow glass microspheres, 2-acrylamido-2-methylpropanesulfonic acid (AMPS) 22 parts, carboxymethyl cellulose 7 parts, and polyphosphoric acid (PPA) 20 parts; the hollow glass microsphere has a ball breakage rate of less than 10%. The hollow glass microspheres include the following two particle sizes: 100-200 μm 42%; 400-500 μm remainder.

[0043] The method for preparing the wear-resistant unglazed polished porcelain tile comprises the following steps:

[0044] 1. Preparation of brick layer: Mix the recycled ceramic powder, sintered fly ash, nano Lu2O3, hydroxyapatite and calcium magnesium silicon composite material, press to obtain the base blank, then sinter at 590℃ for 22min, then sinter at 970℃ for 45min, and finally sinter at 1380℃ for 2.3h; polish after cooling;

[0045] 2. Preparation of enhanced wear-resistant composite materials: adding hollow glass microspheres of 100 to 200 μm and shellac resin to polyphosphoric acid (PPA), placing at 80°C for modification reaction for 1.6 hours to obtain modified shellac resin; then mixing the modified shellac resin, hollow glass microspheres of 400 to 500 μm, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), carboxymethyl cellulose and 112 parts of solvent (water), placing at 108°C for stirring reaction for 1.7 hours to obtain an enhanced wear-resistant composite material;

[0046] 3. Coat the surface of the brick layer with the enhanced wear-resistant composite material and dry it at 72°C to obtain an unglazed polished porcelain tile with a polished surface layer. The thickness of the enhanced wear-resistant layer can be about 0.5 mm.

[0047] Embodiment 5: In some embodiments, a wear-resistant unglazed polished porcelain tile comprises a brick layer and a reinforced wear-resistant layer coated on the surface of the brick layer, wherein the brick layer comprises the following raw materials in parts by weight: 101 parts of recycled ceramic micropowder, 17 parts of sintered fly ash, 3.7 parts of nano Lu2O3, 10 parts of hydroxyapatite, and 26 parts of calcium-magnesium-silicon composite material; the calcium-magnesium-silicon composite material is prepared by high-temperature melting and spinning of calcium stone powder, silica powder, and magnesia, and the composition is: 17% CaO, 19% MgO, and the remainder SiO2; the sintered fly ash is obtained by calcining fly ash at 385°C and then grinding; the reinforced wear-resistant layer comprises the following raw materials in parts by weight: 19 parts of shellac resin, 5 parts of hollow glass microspheres, 20 parts of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 8 parts of carboxymethyl cellulose, and 16 parts of polyphosphoric acid (PPA); the breakage rate of the hollow glass microspheres is less than 10%. The hollow glass microspheres include the following two particle sizes: 100-200 μm 40%; 400-500 μm remainder.

[0048] The method for preparing the wear-resistant unglazed polished porcelain tile comprises the following steps:

[0049] 1. Preparation of brick layer: Mix the recycled ceramic powder, sintered fly ash, nano Lu2O3, hydroxyapatite and calcium magnesium silicon composite material, press to obtain the base blank, then sinter at 550℃ for 15min, then sinter at 920℃ for 42min, and finally sinter at 1340℃ for 2h; polish after cooling;

[0050] 2. Preparation of enhanced wear-resistant composite materials: adding hollow glass microspheres of 100 to 200 μm and shellac resin to polyphosphoric acid (PPA), placing at 77°C for modification reaction for 1.3 hours to obtain modified shellac resin; then mixing the modified shellac resin, hollow glass microspheres of 400 to 500 μm, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), carboxymethyl cellulose and 120 parts of solvent (water), placing at 107°C for stirring reaction for 1.6 hours to obtain an enhanced wear-resistant composite material;

[0051] 3. Coat the surface of the brick layer with the enhanced wear-resistant composite material and dry it at 65°C to obtain an unglazed polished porcelain tile with a polished surface layer. The thickness of the enhanced wear-resistant layer can be about 0.5 mm.

[0052] Comparative Example 1: The difference from Example 5 is that the shellac resin is not modified.

[0053] A wear-resistant unglazed polished porcelain tile comprises a brick layer and a reinforced wear-resistant layer coated on the surface of the brick layer, wherein the brick layer comprises the following raw materials in parts by weight: 101 parts of recycled ceramic micropowder, 17 parts of sintered fly ash, 3.7 parts of nano Lu2O3, 10 parts of hydroxyapatite, and 26 parts of calcium-magnesium-silicon composite material; the calcium-magnesium-silicon composite material is prepared by high-temperature melting and spinning of calcium stone powder, silica powder, and magnesia, and comprises: 17% CaO, 19% MgO, and the balance SiO2; the sintered fly ash is obtained by calcining fly ash at 385°C and then grinding; the reinforced wear-resistant layer comprises the following raw materials in parts by weight: 19 parts of shellac resin, 5 parts of hollow glass microspheres, 20 parts of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), and 8 parts of carboxymethyl cellulose; the ball breakage rate of the hollow glass microspheres is less than 10%. The hollow glass microspheres include the following two particle sizes: 100-200 μm 40%; 400-500 μm remainder.

[0054] The method for preparing the wear-resistant unglazed polished porcelain tile comprises the following steps:

[0055] 1. Preparation of brick layer: Mix the recycled ceramic powder, sintered fly ash, nano Lu2O3, hydroxyapatite and calcium magnesium silicon composite material, press to obtain the base blank, then sinter at 550℃ for 15min, then sinter at 920℃ for 42min, and finally sinter at 1340℃ for 2h; polish after cooling;

[0056] 2. Preparation of reinforced wear-resistant composite material: 100-200 μm hollow glass microspheres, shellac resin, 400-500 μm hollow glass microspheres, 2-acrylamide-2-methylpropanesulfonic acid (AMPS), carboxymethyl cellulose and 120 parts of solvent (water) were mixed, and stirred at 107° C. for 1.6 hours to obtain a reinforced wear-resistant composite material;

[0057] 3. Coat the surface of the brick layer with the enhanced wear-resistant composite material and dry it at 65°C to obtain an unglazed polished porcelain tile with a polished surface layer. The thickness of the enhanced wear-resistant layer can be about 0.5 mm.

[0058] Comparative Example 2: The difference from Example 5 is that the hollow glass microspheres have a uniform particle size of 400 to 500 μm.

[0059] A wear-resistant unglazed polished porcelain tile comprises a brick layer and a reinforced wear-resistant layer coated on the surface of the brick layer, wherein the brick layer comprises the following raw materials in parts by weight: 101 parts of recycled ceramic micropowder, 17 parts of sintered fly ash, 3.7 parts of nano Lu2O3, 10 parts of hydroxyapatite, and 26 parts of calcium-magnesium-silicon composite material; the calcium-magnesium-silicon composite material is prepared by high-temperature melting and spinning of calcium stone powder, silica powder, and magnesia, and comprises: 17% CaO, 19% MgO, and the balance SiO2; the sintered fly ash is obtained by grinding fly ash after calcining at 385°C; the reinforced wear-resistant layer comprises the following raw materials in parts by weight: 19 parts of shellac resin, 5 parts of hollow glass microspheres, 20 parts of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 8 parts of carboxymethyl cellulose, and 16 parts of polyphosphoric acid (PPA); the ball breakage rate of the hollow glass microspheres is less than 10%. The particle size of the hollow glass microspheres is 400-500 μm.

[0060] The method for preparing the wear-resistant unglazed polished porcelain tile comprises the following steps:

[0061] 1. Preparation of brick layer: Mix the recycled ceramic powder, sintered fly ash, nano Lu2O3, hydroxyapatite and calcium magnesium silicon composite material, press to obtain the base blank, then sinter at 550℃ for 15min, then sinter at 920℃ for 42min, and finally sinter at 1340℃ for 2h; polish after cooling;

[0062] 2. Preparation of enhanced wear-resistant composite materials: adding shellac resin to polyphosphoric acid (PPA), placing it at 77°C for modification reaction for 1.3 hours to obtain modified shellac resin; then mixing the modified shellac resin, hollow glass microspheres, 2-acrylamido-2-methylpropanesulfonic acid (AMPS), carboxymethyl cellulose and 120 parts of solvent (water), placing it at 107°C for stirring reaction for 1.6 hours to obtain an enhanced wear-resistant composite material;

[0063] 3. Coat the surface of the brick layer with the enhanced wear-resistant composite material and dry it at 65°C to obtain an unglazed polished porcelain tile with a polished surface layer. The thickness of the enhanced wear-resistant layer can be about 0.5 mm.

[0064] Test Case

[0065] The unglazed polished porcelain tiles prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to performance testing (GB / T 4100-2015). The results are shown in Table 1.

[0066] Table 1 Performance test results

[0067] project Wear resistance Thermal shock resistance Destructive strength (>1300N) Example 1 2100 rpm, level 4 No cracks 4954 Example 2 2100 rpm, level 4 No cracks 4987 Example 3 2100 rpm, level 4 No cracks 5012 Comparative Example 1 1500 rpm, level 3 No cracks 4298 Comparative Example 2 1500 rpm, level 3 Slight cracks 4417

[0068] It can be seen that the unglazed polished porcelain tile of the present invention has high surface hardness, good wear resistance, is not easy to fall off, has good anti-fouling performance, high thermal shock resistance, and high tile strength.

[0069] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A wear-resistant unglazed polished porcelain tile, characterized in that: It comprises a brick layer and a reinforced wear-resistant layer coated on the surface of the brick layer, wherein the brick layer comprises the following raw materials in parts by weight: 75-105 parts of recycled ceramic micropowder, 14-18 parts of sintered fly ash, 1.6-4.0 parts of nano Lu2O3, 5-11 parts of hydroxyapatite, and 12-27 parts of calcium magnesium silicon composite material; The enhanced wear-resistant layer comprises the following raw materials in parts by weight: 14-21 parts of shellac resin, 4-7 parts of hollow glass microspheres, 18-25 parts of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), 4-10 parts of carboxymethyl cellulose, and 14-21 parts of polyphosphoric acid (PPA).

2. The wear-resistant unglazed polished porcelain tile according to claim 1, characterized in that: The calcium-magnesium-silicon composite material is prepared by high-temperature melting and spinning of calcium stone powder, silica stone powder and magnesia, and has the following components: 15-18% CaO, 15-20% MgO and the balance SiO2.

3. The wear-resistant unglazed polished porcelain tile according to claim 2, characterized in that: The sintered fly ash is obtained by calcining fly ash at 330-400° C. and then grinding it.

4. The wear-resistant unglazed polished porcelain tile according to claim 3, characterized in that: The particle size of the hollow glass microspheres is 100-500 μm, and the ball breakage rate is less than 10%.

5. The wear-resistant unglazed polished porcelain tile according to claim 4, characterized in that: The hollow glass microspheres include the following two particle sizes: 100-200 μm 32-48%; 400-500 μm remainder.

6. The wear-resistant unglazed polished porcelain tile according to claim 5, characterized in that: The weight ratio of the shellac resin to polyphosphoric acid (PPA) is controlled at 1:

1.

7. A method for preparing the wear-resistant unglazed polished porcelain tile according to claim 6, characterized in that: The following steps are involved:

1. Preparation of Brick Layer Mix 75-105 parts of recycled ceramic micropowder, 14-18 parts of sintered fly ash, 1.6-4.0 parts of nano-Lu2O3, 5-11 parts of hydroxyapatite, and 12-27 parts of calcium-magnesium-silicon composite material, press to obtain a base blank, and cool after sintering; 2. Preparation of reinforced wear-resistant composite materials Adding hollow glass microspheres of 100 to 200 μm and shellac resin to polyphosphoric acid (PPA), and subjecting the mixture to a modification reaction at 75 to 81° C. for 1 to 3 hours to obtain a modified shellac resin; then mixing the modified shellac resin, hollow glass microspheres of 400 to 500 μm, 18 to 25 parts of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 4 to 10 parts of carboxymethyl cellulose and 90 to 130 parts of a solvent, subjecting the mixture to a stirring reaction at 105 to 110° C. for 1.3 to 2 hours to obtain a reinforced wear-resistant composite material; 3. Coating the reinforced wear-resistant composite material on the surface of the brick layer and drying it to obtain an unglazed polished porcelain tile with a polished surface layer.

8. The method for preparing the wear-resistant unglazed polished porcelain tile according to claim 7, characterized in that: The drying temperature is 60-75℃.

9. The method for preparing the wear-resistant unglazed polished porcelain tile according to claim 8, characterized in that: Sintering includes the following steps: Sinter at 500-600°C for 10-25 min, then sinter at 900-1000°C for 30-50 min, and finally sinter at 1300-1400°C for 1.5-2.5 h.

10. The method for preparing the wear-resistant unglazed polished porcelain tile according to claim 9, characterized in that: After sintering, cooling and polishing, the reinforced wear-resistant composite material is coated on the surface of the brick layer.

Citation Information

Patent Citations

  • Preparation method of composite thermal insulation material

    CN105967716A

  • Natural granite-imitated ceramic tile material and preparation method thereof

    CN112250307A

  • Wear-resistant tempered glass and preparation method thereof

    CN118529945A

  • Tooth coating liquid

    KR1020010089957A

  • Light weight structural materials

    TW201430029A